[Tecfidera® (delayed-release dimethylfumarate) in the treatment of relapsing-remitting multiple sclerosis] - Mantovani, Lorenzo Giovanni; Furneri, Gianluca; Cortesi, Paolo Angelo; Amato, Maria Pia; Caputi, Achille Patrizio; Piacentini, Patrizio; Solari, Alessandra; Pozzilli, Carlo; Comi, Giancarlo (Farmeconomia. Health economics and therapeutic pathways, 2017)
The present health technology assessment (HTA) evaluates the clinical and economic profile of delayed-release dimethylfumarate (DMF, also known as gastro-resistant DMF) in the treatment of relapsing-remitting multiple sclerosis (RRMS) in Italy. Chapter 1 briefly introduces the condition (multiple sclerosis and, more specifically, the relapsing-remitting form) and provides an overall description of the main therapeutic options for physicians, in terms of clinical evidence, regulatory status in Europe and approval status and reimbursement (refunding) criteria in Italy. In the next sections (Chapters 2-5), key-topics regarding RRMS are analysed: epidemiology, clinical burden, quality of life/social impact and the economic implications for healthcare services, patients and society. In Chapter 6, the clinical evidence supporting the use of DMF in RRMS is summarized. Data from phase III randomized clinical trials (DEFINE, CONFIRM), plus the pooled post-hoc analysis of the two studies, were evaluated to assess the level of clinical benefit provided by DMF. Finally, in Chapter 7, a review of the health economic evidence assessing DMF is performed, with a specific focus on Italy. Overall, the methodological quality of registration studies, together with the robustness and consistency of the study results, support the conclusion that DMF is an effective and safe treatment for RRMS. The economic assessment of DMF in Italy, based on cost-effectiveness and budget impact analyses (adopting clinical input data from a mixed treatment comparison and economic input data relative to the Italian healthcare setting), confirm that DMF is a cost-effective and economically sustainable treatment for the Italian National Healthcare Service. These findings are in line with the results of most international publications and the assessments from well-recognized HTA agencies (e.g. NICE/SMC). In summary, both the clinical and economic evidence analyzed in this HTA substantiate DMF as an important therapeutic option for the treatment of RRMS.